Perancangan Motorcyle Lift Dinamo Sebagai Alat Bantu Mekanik Ergonomis Dalam Service Motor Umum - Yoseph; Gregorius Alfin Priambudi; Evelyn Rusady; Erlandy Yahya Sinaga; Marcilinus Arikurniawan; Firman Alamsyah (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2020)
Jaya Abadi Motor Workshop business does motorbike servicing work with bad working postures, which are standing while bending, sitting, and squatting, causing muscle injury(Musculoskeletal Disorders) for 4 mechanics. For this reason, it is necessary to design a work facility for efficient motorbike service. The Nordic Body Map (NBM) questionnaire was used to find out the percentage of body parts that experienced no pain, sufficient pain, pain and evaluation. With NBM comparisons before and after, this will be a reference to improve operator work posture for the better. The results of the design of the tool in the form of a motorcycle lift that is useful to position the height of the motor as set with the needs of the operator (calculation of anthropometry with 5% percentile of 855 mm from the ground), there is a dynamo as an additional automation of the propulsion and there is still a hydraulic lever for backup when the dynamo switch is broken , so that helps in the process of setting the motor high and low. Based on testing the NBM results are lower (down 50% and partly down 25% from 100%), so that the working posture is better and the facility can be utilized to service motorcycles only for the type of motorcycle.